Phase evolution, microstructure and electrical response of KNNT ceramics with Li+ substitution and doping - Surirat Yotthuan; Thanya Udeye; Sasiphon Prasertpalichat; Phieraya Pulphol; Naratip Vittayakorn; Theerachai Bongkarn (Ferroelectrics, 2022)
Lead-free (K0.5Na0.5)(Nb0.7Ta0.3)O3 (KNNT) ceramics with Li+ substitution (KN0.5-xLixNT) and direct (KNNT-xLi) doping at x = 0, 0.01, 0.02, 0.03 and 0.04 mol% were synthesized by the solid-state combustion route. The phase, microstructure, dielectric and ferroelectric properties of the ceramics were examined. The XRD pattern of the ceramics revealed orthorhombic and tetragonal phases in all specimens. The Rietveld refinement procedure showed that increasing either the Li+ substitution or doping levels enhanced the amount of the tetragonal phase. It was found that Li+ doping, either substitutional or additional, enhanced the Curie temperature (TC) by increasing the tetragonal distortion, while the dielectric constant (εC) decreased. The good remanent P-E loops of the KN0.5-xLixNT ceramics were found with x = 0.01 (Pr∼10.89 µC/cm2 and EC∼13.09 kV/cm), while for KNNT-xLi ceramics, it was obtained with x = 0.02 (Pr∼15.65 µC/cm2 and EC∼11.46 kV/cm), which were confirmed by remanent P-E hysteresis measurements.
Keywords: Ferroelectric and Piezoelectric Materials; Microwave Dielectric Ceramics Synthesis; Dielectric properties of ceramics